INOVASI MESIN PENGHALUS REMPAH-REMPAH UNTUK PENINGKATAN EKONOMI MASYARAKAT DI KOTO ANAU KABUPATEN SOLOK - Oknovia Susanti; Muhammad Khalid Al Mujaahid; Muhammad Alif Alhadid; Dedison Gasni (LPPM Universitas Andalas, 2025)
Spices have long been an integral part of human life, playing a vital role as traditional medicine, culinary ingredients, and components in cosmetics. Indonesia, particularly within the Southeast Asian region, is regarded as a global hub for high-quality spices. One such spice-rich area is Nagari Koto Anau, located in Solok Regency, known for its production of cloves and cinnamon. However, this significant potential has yet to be fully harnessed by local farmers due to limited processing technology—particularly the lack of spice grinding machines. As a result, farmers are only able to sell their spices in raw form at low market value, which adversely affects their income. To address this issue, the design and implementation of a spice grinding machine that can be operated directly by farmers is essential. The aim of this activity is to accelerate the spice processing workflow, improve work efficiency, and enhance the added value of spice products at the local level. The programme was carried out in Nagari Koto Anau, Solok Regency, West Sumatra Province. The methods employed included interviews, equipment design, and training on the use of the spice grinding machine. Interviews involved discussions with farmers to identify their problems and offer practical solutions, followed by designing the machine based on their specific needs. The training method included a hands-on demonstration on how to operate the spice grinder. The results showed that the spices processed using the grinder became fine and evenly ground, with a production output of up to 20 kilograms.